Improving Resident Well-Being During Shiftwork: Are Casino Shifts the Answer?. Issue 12 (December 2019) - Levin, Helen; Lim, Rodrick; Lynch, Timothy; Sangha, Gurinder
Abstract : Purpose: The objective of this study is to quantitatively evaluate the well-being of residents doing casino shifts compared with those doing standard overnight shifts while working in an academic pediatric emergency department. Methods: A randomized prospective survey study was performed over a period of 1 year on all residents who were scheduled to complete a 28-day block. Each block (28-day period) within the year was designated as either a "standard" or "casino" block. The standard overnight shifts were scheduled from midnight to 0800 hours, and casino shifts occurred from either 2000 to 0400 hours (casino A) and 0400 to 1200 hours (casino B). Participating residents were asked to complete both a preblock and postblock survey. The primary outcome was defined as differences in resident well-being as assessed by the brief resident wellness profile (BRWP). A mood faces graphical rating item to assess overall mood was used as a secondary outcome measures as well as a 10-item survey based on World Health Organization domains for quality of life and adapted to reflect completion of shiftwork. Results: A total of 124 (90%) of 138 residents completed the study and were included in the analysis. No significant difference in resident well-being measured by BRWP between those in the standard and casino shift groups (17 ± 2.5 for preblock standard and 16.9 ± 2.8 for casino, P = 0.904; 17.1 ± 2.7 for postblock standard and 17.2 ± 3.1 for casino, P = 0.817), or in the relative change of the BRWP preblock and postblock between the 2 groups (standard, 0.35 ± 2.7; casino, 0.29 ± 3.0; P = 0.926). No significant difference in the mood faces rating scale scores or the 10-item postblock survey was found. Conclusions: In the first study examining the effects of casino shifts on trainees, we found no effect of standard overnight versus casino shifts on their well-being. This counters the benefits previously seen in emergency department consultant staff and highlights the need for more studies specifically in trainees.